A "NOBREZA DA TERRA": a constituição de uma elite local na capitania de São José do Piauí – do final do século XVII ao final do século XVIII. - Fonseca, Rodrigo Gerolineto (Outros Tempos: Pesquisa em Foco - História, 2012)
This paper analyzes the power relations in the Captaincy of São José do Piauí, as well as strategies for establishing a local political power. To do so, exposes the contrast between the configuration of stockyard’s society, since the end of the century XXVII, and the context of the government's installation of the captaincy, in the second half of the eighteenth century. It is considered one of the oldest documents in the history of Piaui: a Description of the Piauí’s hinterland, written by priest Miguel de Carvalho in 1697. Then, from documents produced in the sphere of colonial administration, seeking to investigate the strategies adopted in the formation of a local elite that served the purposes of the metropolis. Among these strategies, we highlight the economic benefits and social prestige as important elements  that have come to mediate power relations.